2005
DOI: 10.1128/jvi.79.1.393-400.2005
|View full text |Cite
|
Sign up to set email alerts
|

CD8+T-Cell-Mediated Cross-Clade Protection in the Genital Tract following Intranasal Immunization with Inactivated Human Immunodeficiency Virus Antigen Plus CpG Oligodeoxynucleotides

Abstract: Human immunodeficiency virus (HIV) is a mucosally transmitted infection that rapidly targets and depletes CD4؉ T cells in mucosal tissues and establishes a major reservoir for viral persistence in gut-associated lymphoid tissues. Therefore, vaccines designed to prevent HIV infections must induce potent and durable mucosal immune responses, especially in the genital tract. Here we investigated whether intranasal (i.n.) immunization with inactivated gp120-depleted HIV-1 antigen (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
30
1
2

Year Published

2006
2006
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 43 publications
(43 reference statements)
0
30
1
2
Order By: Relevance
“…In this sense, the different mucosal routes of immunization, such as the oral, intranasal, rectal, and vaginal routes, may play an important role, since they can induce generalized mucosal immune responses not only at the site where they are administered but at distal mucosal effector sites as well. It is well-known that intranasal immunization can elicit immune responses in respiratory tract and genital mucosal tissues in mice, monkeys, and humans (58,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…In this sense, the different mucosal routes of immunization, such as the oral, intranasal, rectal, and vaginal routes, may play an important role, since they can induce generalized mucosal immune responses not only at the site where they are administered but at distal mucosal effector sites as well. It is well-known that intranasal immunization can elicit immune responses in respiratory tract and genital mucosal tissues in mice, monkeys, and humans (58,59,60).…”
Section: Discussionmentioning
confidence: 99%
“…[46][47][48] A few reports in prime-boost protocols described the use of recombinant vaccinia virus following antigenic peptide and CpG ODN to promote the CTL responses. 49,50 It will be interesting to understand if the dichotomy (suppressed CD81 T cell responses of enhanced anti-tumor immunity) is unique to adenovirus in combination with CpG ODN since adenovirus is a DNA virus and may activate TLR9 on its own or other TLR ligands that interact with TLR9 pathway. DCs and macrophages are known to be able to cross-present virus like particles.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown that the routes of viral immunization can affect the characteristics of induced T-cell responses (3,4,20). For example, intrarectal immunization of mice with human immunodeficiency virus type 1 (HIV-1) peptides induced a CTL response in the Peyer's patches (PP), the spleen, and lamina propria of the intestine, and these responses were able to reduce the viral titer in the ovaries and the colorectal tissue upon intrarectal HIV-vaccinia virus challenge (3).…”
mentioning
confidence: 99%